On Binary Representation of Integers. Issue 5 (28th May 2019) - Melkonian, Vardges
Abstract: This paper discusses a game that can be used for introducing the binary representation of integers in an interactive and fun environment. The game is introduced in the way it is presented in an undergraduate Discrete Mathematics class. Variations of the game are discussed, particularly its extension to base-three representation of integers. It is also shown how the game can be used for discussing other discrete mathematics topics such as counting techniques.